CORPORATE SOCIAL REPORTING AS APPENDIX TO FINANCIAL STATEMENT - I. Derun (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The paper deals with essence and importance of corporate social reporting in the management of business entity management. The study examines several approaches for providing data about economic, ecological and social aspects of the companies. There are approaches of formulating of separated reports as addition to financial statements (for example Value Added Statement, Intellectual Capital Statement) and integrated reporting. The article examines positive and negative factors that could significantly influence the implementation process of corporate social reporting for companies in Ukraine and around the world. Principles of corporate social reporting are considered. The research analyzes methodical approaches of preparing of integrating statements for large companies and data needs of stakeholders for making effective management decisions.